Comportamento do consumidor de alimentos: uma análise do consumo de carnes em São Paulo - Raimundo, Lívia Maria Borges (2013)
The meat production chain is a major agro-industrial chains in Brazil and also in the world. Its survival is fundamentally based on its ability to generate and sustain competitive advantage, resulting in value to the final consumer. The per capita consumption of meat (beef, pork and chicken) is growing up in Brazil, and data show that in last twenty years there has been growth of 81%, achieving 80 kilos per capita in 2007. The studies that seek to understand consumer behavior can be translated into strategies and tactics that increase the competitiveness of the entire production chain, since through the purchase the customer transmits information about quality attributes he desires and its acceptability. This study investigated the behavior of the ultimate consumer of beef, pork and chicken in the city of São Paulo, in order to obtain information that support marketing strategies for companies in the sector. From a review of literature about food consumption behavior, focused on meat consumption, the lifting of national research on the topic, as well as a characterization of the productive chains of the three meats in question, were listed the main variables affecting the consumption of meat products. With this basis, a survey was conducted with 400 individuals in São Paulo, during the months of September, October and November 2012. The sample, stratified and probabilistic, was treated with univariate and multivariate analysis (factor and cluster), which allowed the grouping of similar variables and the investigation of dependence between them. It was observed that the bovine meat is preferred by the consumers, followed by the chicken and pork. For beef and pork, there was no relationship between frequency of consumption and income, which confirms the growing influence of nonprice factors on consumption at the expense of economic variables. The chicken meat was the best rated in the category impact on health, and its nutritional composition is best known by consumers. The principal place of purchase of the three meats consists at the supermarket, followed by the butcher. Five clusters of consumers were characterized with different consumption profiles, the economic, the conventional, the demanding, the moderate and the enlightened, performing at different frequencies for each meat in question. The study contributed as an overview of consumer behavior meat in São Paulo, where can be characterized different consumption profiles for each meat in question. Knowing these profiles becomes important once the consumer is the maintainer agent and the driver of financial trends of the entire production chain.